Mixed epithelial and stromal tumor of the kidney - Raphael Hart Lyngdoh; Maria Bukelo; Muktha R Pai (Wolters Kluwer Medknow Publications, 2013)
Mixed epithelial and stromal tumor (MEST) of the renal pelvis or the older terminology cystic hamartoma of renal pelvis is a rare benign tumor and recently been recognized as a distinct clinical and pathological entity. These complex neoplasms are composed of a mixture of stromal and epithelial elements and are seen predominantly in women (ratio of women to men 6:1) and are generally seen in perimenopausal women with presenting symptoms of flank pain, hematuria or symptoms of urinary tract infection. We present here a case of MEST in a 48-year-old female who presented with a mass per abdomen associated with a mild dragging pain of 6 months duration. The ultrasonography report was of a multi-cystic lesion in the right kidney. Surgical excision of the lesion showed a mass measuring 18 × 14.5 × 7 cm with attached normal ureter. The outer surface was bosselated and showed multiple-cystic nodules with pale brown to dark brown smooth and glistening surface. The tumor was well circumscribed and there were multiple cysts of varying sizes separated by stroma arising from the dilated pelvicalyceal system. The wall of the cysts are covered by papillary excrescences. On histological examination, a well delineated tumor composed of cysts of varying sizes lined by columnar, cuboidal and transitional epithelium. Surrounding stroma showed a mixture of ovarian type of stroma and spindle shaped cells of smooth muscle type having plump nuclei. Sections from the renal-tissue adjacent to the tumor showed normal glomeruli and tubules.